The Ideological Content and Architectural Features of Drinking Fountains - Gayane Nahapetyan; Lyuba Kirakosyan (Journal of Architectural and Engineering Research)
In the late Middle Ages and until the beginning of the 20th century, the drinking fountain was one of the economic and cultural structures of the settlement. After the Sovietization of Armenia and especially during and after the Patriotic War, when monument-building was encouraged, favorable conditions were created for the construction of springs and especially spring-monuments. In Armenia today, memorial fountains come in a wide variety of forms and are placed in various locations for various purposes.  Their ideological content and structural, figurative analysis have not yet been fully explored in the thematic literature. Since these monuments already form a sizable group in material terms, we believe it is essential to discuss the subject and fully unveil the image, to present a comprehensive study of the process of forming monumental fountains as a materialized product of memory. This work aims to present the memorial fountains' plan, spatial composition, typology, and characteristics,  as well as the reasons behind their construction. It also attempts to address their ideological content, installation motives, compositional, structural and artistic features, to expose the cultural perception of memorial fountains, which is closely linked to the cult of water and the materialization of memory. The study used the landscape research method, based on analysis, data collection, and synthesis of interdisciplinary studies. The method also included work with literature, which made it possible to trace the historical development of memorials as separate monumental structures.